The Role of Cytochrome P450 in Fish Health and Metabolism: A Vital Enzyme System (Journal of Fish Health, 2025)
Cytochrome P450 (CYP450) enzymes are vital enzymes in the metabolic processes of fish, playing a crucial role in the detoxification of xenobiotics and the regulation of endogenous compounds. The biotransformation of pollutants, including pesticides, medicines, and polycyclic aromatic hydrocarbons (PAHs), which build up in aquatic environments, is facilitated by these enzymes, especially those in the CYP1A, CYP2, and CYP3A families. Immunity of fish and their health, can be negatively impacted by metabolic byproducts, which can occasionally be more toxic than the original compounds even though CYP450 activity helps with detoxification. Exposure to pollutants and other environmental stressors can alter the expression and activity of CYP enzymes, which can cause physiological disruptions in fish species. This review explores the key roles of CYP450 enzymes in fish metabolism and health, emphasizing their importance as biomarkers for environmental toxicity and their potential impact on aquatic ecosystems. Assessing the effects of environmental contaminants and creating plans for environmental preservation and fish health management require an understanding of CYP450 mediated metabolic pathways in fish.
Keywords: Cytochrome P450; Metabolism; Ecotoxicology; Aquatic Animal Health